The aesthetics of wine - Burnham, Douglas; Skilleås, Ole Martin (Chichester, West Sussex ; Hoboken : John Wiley & Sons, 2012)
"The Aesthetics of Wine shows that discussing wine within the framework of aesthetics both benefits our understanding of wine as a phenomenon, while also challenging some of the basic assumptions of the tradition of aesthetics. Analyzes the appreciation of wine as an aesthetic practice. Tackles prejudices against bodily senses, showing how they distort traditional aesthetic theory Represents the beginnings of a reformulation of general aesthetics"--
"Analyzes the appreciation of wine as an aesthetic practice"--
Basic Concepts -- Wine as a Vague and Rich Object -- Wine and Cognition -- Aesthetic Attributes in Wine -- Taste and Expertise in Wine -- The Wineworld.
Machine generated contents note: Introduction 1. Basic Concepts 2. Wine as an Object 3. Wine and Cognition 4. Aesthetic Attributes 5. Taste and Expertise 6. The Wineworld Bibliography.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Wine -- Philosophy; Wine tasting; PHILOSOPHY -- Aesthetics; Electronic books